Elaboración de un radiofármaco (Parte I): Preparación de un ligando del tipo diaminoditiol para uso en medicina nuclear - López-Gabriel, J. (2002)
In the renal function study the diaminodithiol (DADT) complexes with Tc 99m have an advantage due to the great absortion in the kidneys and the fast removal by means of urine. Among this complexes, the N,N´-bis-L-(1-carboxi-2-mercaptoethyl) ethylendiamine (EC) witch form an stable complex with oxotechnetium (V) of tetragonal structure exhibit better results. In this work a study about its preparation is presented.